Nursing care management for active Pulmonary Tuberculosis patients in an inpatient ward a case study at Monompia GMIBM Hospital Kotamobagu - Mongilong, Gina F.; Jaata, Jikrun; Patonengan, Gita S. (Privietlab, 2026)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis that often manifests in the lungs. The symptoms of pulmonary tuberculosis include coughing up phlegm for 3-4 weeks or more, shortness of breath, weight loss, night sweats without activity, and fatigue. If not immediately provided with nursing care, the impact of pulmonary tuberculosis can result in severe hemoptysis, which can cause death due to hypovolemic shock and airway obstruction. This case study aimed to analyze the nursing care provided to patients with active pulmonary tuberculosis in the Bethesda Ward of Monompia GMIBM Hospital, Kotamobagu. This research method uses a descriptive analysis with a case study approach. The subject in this case was a patient with active pulmonary tuberculosis in the inpatient ward of the Bethesda Ward of Monompia GMIBM Hospital. Kotamobagu. The study results showed that the nursing care management for pulmonary TB patients with nursing problems carried out by the researcher included ineffective airway management for airway clearance, hypovolemia management for hypovolemia, sleep support for sleep disturbances, energy management for activity intolerance, and nutrition management for the risk of nutritional deficits. The interventions included observation, therapy, education, and collaboration with other departments.